Performance and Egg Quality of Laying Hens Fed Ration Containing Coriander Seeds (Coriandrum sativum Linn) - Umul Habiyah; R. Mutia; S. Suharti (Media Peternakan, 2016)
The aims of this study were to determine the effect of diets containing different levels of coriander seeds on performance and egg quality of Lohmann Brown laying hens. A total of 96 Lohmann Brown laying hens of 43 weeks of age were randomly allocated into 16 experimental units by assigning a completely randomized design with 4 treatments and 4 replications that kept for 6 weeks. The treatment diets were R0: diet with 0% supplementation of coriander seeds powder (control), R1: diet with supplementation of 1% coriander seeds powder, R2: diet with supplementation of 2% coriander seeds powder, and R3: diet with supplementation of 3% coriander seeds powder. The results showed that supplementation of coriander seeds in diets did not affect egg weight, egg production, and egg mass. Supplementation of coriander seeds 2%-3% significantly (P<0.05) decreased feed consumption and feed conversion ratio. Supplementation of coriander seeds 1%-3% significantly (P<0.05) increased yellowness in yolk color without affecting other quality parameters. It can be concluded that supplementation of coriander seeds at the levels of 2%-3% decreased feed intake, feed conversion ratio, and increased yolk color, however, the supplementation at all levels in diets did not affect egg weight, egg production, and egg mass.